PENGARUH CAPITAL INTENSITY, FINANCIAL PERFORMANCE DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE - Siregar, Desi; Setyawati, Wiwit (Publika Citra Media, 2025)
This study aims to analyze the influence of capital intensity, financial performance and transfer pricing on tax avoidance This research was conducted on consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023, consisting of 125 data. The sample was taken using the purposive sampling technique, resulting in a sample of 23 companies with observation for 5 (five) years. The data used in this study is secondary data in the form of financial statements from each company that has been used as a research sample. The data analysis method uses panel data regression analysis. The test tool used is the E-Views 12 version program. Based on the results of hypothesis testing, it is shown that capital intensity, financial performance and transfer pricing simultaneously have a significant influence on tax avoidance. Partially, only financial performance does not have a significant influence on the on tax avoidance, while capital intensity and transfer pricing have a significant influence on tax avoidance.